2017
DOI: 10.4103/pm.pm_232_16
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective flavonoids in Opuntia ficus-indica fruits by reducing oxidative stress in primary rat hepatocytes

Abstract: Background:Liver disorder was associated with alcohol consumption caused by hepatic cellular damages. Opuntia ficus-indica fruit extracts (OFIEs), which contain betalain pigments and polyphenols including flavonoids, have been introduced as reducing hangover symptoms and liver protective activity.Objective:To evaluate hepatoprotective activity of OFIEs and isolated compounds by high-speed countercurrent chromatography (HSCCC).Materials and Methods:The extract of O. ficus-indica fruits was fractionated into met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(2 citation statements)
references
References 24 publications
(24 reference statements)
1
1
0
Order By: Relevance
“…No previous studies have investigated the effect of taxifolin on tGSH in the lung tissue or its effect on DNA oxidative damage. One study reported that GSH protected the liver tissue against ethanol-induced oxidative damage by preventing its reduction [27]. The results of the present study showed that taxifolin protected DNA from oxidative damage.…”
Section: Discussionsupporting
confidence: 65%
“…No previous studies have investigated the effect of taxifolin on tGSH in the lung tissue or its effect on DNA oxidative damage. One study reported that GSH protected the liver tissue against ethanol-induced oxidative damage by preventing its reduction [27]. The results of the present study showed that taxifolin protected DNA from oxidative damage.…”
Section: Discussionsupporting
confidence: 65%
“…Jordanian fruit juice at 2 mL/kg bd administration reduced liver damage induced by Cyclophosphamide (CP) in mice [ 143 ]. N-butanol fractioned flavonoids at 10 and 100 µg/mL protected Sprague-Dawley rat hepatocytes against alcoholic oxidative stress, increasing cell viability up to 40% [ 144 ].…”
Section: Resultsmentioning
confidence: 99%